Gerações drag queens em Campo Grande: entre espaços, memórias, disputas e (re)afirmações - WINNY GABRIELA PEREIRA DE SANTANA (2021)
This research focus on the analysis of the drag queen art development from tensions, approaches and displacement between two generations of drag artist — the Bistrot Generation and the Current Generation — crucial to comprehend this artistic activity in the city of Campo Grande-MS. Therefore, it was necessary the analysis of the Bistrot Dance nightclub, in operation since the early 2000s and considered the first “GLS nightclub” in the city. The space, now closed, remains in the imaginary of the two generations of artists who consider it one of the most relevant points to understand the “homosexual trajectory” of a city with a restricted “GLS scene”. From a theoretical-methodological point of view, a bibliographic survey was carried out with authors that address topics such as generation, drag queen art, trajectory and memory. The field developed from ethnographies in places that currently shelter(house) drag art in the city, such as: LGBT parade, nightclubs, drag queen contests and Miss Gay contest. From this field, an interlocutors network was established, which, after the narrowing of the relationship, made it possible to conduct semi-structured interviews with artists of both generations. As a result of the research, it was possible to verify that the two generations of artists take different spaces in the “scene” of the city and that there was a change both in the places occupied by the drag art and the performance itself. These changes are related to their social places, built from the intersection between some social markers of difference. It was also observed that the occupation of these spaces is intrinsically related to the subjectivation process of the two generations of drag artists and to the strategies for visibility created by them to make themselves visible in the “scene”.